The late age of print: everyday book culture from consumerism to control - Striphas, Ted (Columbia University Press, 2011)
Ebook from IG Library; Includes bibliographical references and indexes; At the renowned, international literary conference hosted by Villa Gillet and Le Monde, organizers asked more than seventy prominent authors to choose a word that opens a door to their work. Their musings, collected here for the first time, offer an extraordinary portrait of writing and reading from the novelist's perspective. Organized alphabetically by keyword, the anthology is filled with intriguing, amusing, and often surprising insight, essential to an intimate understanding of literature.